Assessment of the Effect of Sorafenib on Omega-6 and Omega-3 Epoxyeicosanoid Formation in Patients with Hepatocellular Carcinoma - Leineweber, Can G. (Int J Mol Sci, 2020)
Hepatocellular carcinoma (HCC) is a leading cause of cancer death. The multikinase inhibitor sorafenib is widely used for systemic therapy in advanced HCC. Sorafenib might affect epoxyeicosanoids, as it is also a potent inhibitor of the soluble epoxide hydrolase (sEH), which catalyzes the conversion of epoxides derived from long-chain polyunsaturated fatty acids (PUFAs), such as arachidonic acid (AA) and omega-3 docosahexaenoic acid (DHA), into their corresponding diols. Experimental studies with AA-derived epoxyeicosatrienoic acids (EETs) showed that they can promote tumor growth and metastasis, while DHA-derived 19,20-epoxydocosapentaenoic acid (19,20-EDP) was shown to have anti-tumor activity in mice. In this pilot study, we assessed the effect of sorafenib treatment on the presence of lipid mediators, such as EETs, in blood of the patients with HCC using the lipidomics technology. We found a significant increase in 11,12-EET and 14,15-EET levels in HCC patients treated with sorafenib. Furthermore, while not significant in this small sample set, the data presented indicate that sorafenib can also increase the level of omega-3 DHA-derived 19,20-EDP. While the effect on EETs might hamper the anti-tumor effect of sorafenib, we hypothesize that supplementation of DHA in sorafenib-treated HCC patients could increase the level of 19,20-EDP and thereby enhance its anti-tumor effect.